Energy Consumption, Information and Communication Technology and Economic Growth in an African Context - Chimbo, Bester (International Journal of Energy Economics and Policy, 2020)
The study had two main objectives. Firstly, to investigate the impact of ICT on economic growth. Secondly, to explore whether energy consumption and human capital development are channels through which ICT influences economic growth in Africa. Whilst literature is unanimous when it comes to the positive impact of ICT on economic growth, not much has been investigated on the impact of the complementarity between (1) ICT and energy consumption and (2) ICT and human capital development on economic growth, especially in the African context. The current study used fixed effects, random effects, pooled OLS and the dynamic GMM with annual panel data ranging from 2001 to 2015. Whilst fixed and random effects show a significant positive relationship running from ICT towards economic growth, pooled OLS and the dynamic GMM produced results which show that ICT had a non-significant positive influence on economic growth in Africa. The interaction between ICT and energy consumption had a significant negative effect on economic growth across all the panel data analysis methods. The finding means that ICT enhanced economic growth through its energy efficiency impact in Africa, consistent with Lee and Brahmasrene (2014). The interaction between ICT and human capital development was found to have had a significant positive effect on economic growth in Africa, in line with Ortiz et al. (2015) whose study revealed that the complementarity between ICT and education enhanced economic growth. The study therefore urges the African continent authorities to develop, strengthen and implement sound human capital development in order to enhance the impact of ICT on economic growth. African countries are also urged to implement sound ICT growth policies in order to trigger energy efficiency led economic growth. Keywords: ICT, Energy Consumption, Human Capital Development, Africa JEL Classifications: N7, Q4, E44, O55 DOI: https://doi.org/10.32479/ijeep.8118